KONTRUKSI IJTIHAD MUHAMMADIYAH MENGENAI PROBLEM KONTEMPORER KOTA AMBON - Laisouw, Yusup (TAHKIM, 2023)
As a reformist or reformer movement, Muhammadiyah has an agenda to create a new, modern and rational Muslim society, or in Ahmad Dahlan's language it is called a progressive Muslim society. This expression contains a signal of the emergence of a new society, including women who are different from the existing figures. There were three contested gender constructions in the early days of Muhammadiyah's founding, namely colonial, priyayi, and merchants with urban santri backgrounds. These three constructions have an influence, both absorbed (received) and neglected (abandoned), on Muhammadiyah's gender construction process. The women's movement in the Muhammadiyah organization is now continuing to spread to all regions in Indonesia. Not only is it growing rapidly in the western region, the women's movement in this organization has also spread to the eastern region of Indonesia, namely in Maluku Province, especially in Ambon City. This can be seen from the participation of Muhammadiyah figures in Ambon City in efforts to empower women through semi-autonomous Muhammadiyah institutions namely 'Aisyiah and Naisyiatul Aisyiah. Muhammadiyah pluralism is Muhammadiyah which is a place of interaction between various groups who respect each other. Muhammadiyah is open and accepts differences as sunnatullah.